Cement industry ”“ Associated emissions, environmental issues and measures for the control of the emissions - Francis B. Elehinafe; Somina N. Ezekiel; Oyetunji B. Okedere; Olayemi O. Odunlami (Mechanical Engineering for Society and Industry, 2022)
The cement industry though the backbone of modern construction and civilization is associated with the emission of diverse atmospheric pollutants with numerous attendant effects on the balance of ecosystem, human and environmental health and the global climate in general. Despite the huge advantages derivable from the industry, exploitation and processing of cement must be done in a sustainable manner to prevent irreversible damage to human, animal and vegetation health as well as the environment. Research papers were reviewed from different databases like ScienceDirect, ResearchGate, Google scholar, and Scopus the chief air pollutants are the inorganic gaseous emissions (carbon dioxide (CO2), carbon monoxide (CO), oxides of nitrogen (NOx), oxides of sulphur SO2), particulates of various size ranges and elemental emissions. The present study carries out holistic review of the cement production process with a view to identifying the principal air pollutants, sources and associated environmental issues. The study also reviews the pollution control measures currently in use and calls for a concerted effort from researchers, industry operators and regulators at working to reduce emissions with a view to upholding environmental sustainability.